Sri Krishna, the Lord of Guruvayur - Vaidyanathan, K. R. (Kunissery Ramakrishnier), 1926- (Bhavan's book university, 1977)
Descriptive study of the temple at Guruvayur, Kerala, and the greatness of Guruvayurappan form of Krishna, Hindu deity.